Infant Mortality Risk and Paternity Certainty Are Associated with Postnatal Maternal Behavior toward Adult Male Mountain Gorillas (Gorilla beringei beringei). - Stacy Rosenbaum; Jean Paul Hirwa; Joan B Silk; Linda Vigilant; Tara S Stoinski (PLoS ONE, 2016)
Sexually selected infanticide is an important source of infant mortality in many mammalian species. In species with long-term male-female associations, females may benefit from male protection against infanticidal outsiders. We tested whether mountain gorilla (Gorilla beringei beringei) mothers in single and multi-male groups monitored by the Dian Fossey Gorilla Fund's Karisoke Research Center actively facilitated interactions between their infants and a potentially protective male. We also evaluated the criteria mothers in multi-male groups used to choose a preferred male social partner. In single male groups, where infanticide risk and paternity certainty are high, females with infants <1 year old spent more time near and affiliated more with males than females without young infants. In multi-male groups, where infanticide rates and paternity certainty are lower, mothers with new infants exhibited few behavioral changes toward males. The sole notable change was that females with young infants proportionally increased their time near males they previously spent little time near when compared to males they had previously preferred, perhaps to encourage paternity uncertainty and deter aggression. Rank was a much better predictor of females' social partner choice than paternity. Older infants (2-3 years) in multi-male groups mirrored their mothers' preferences for individual male social partners; 89% spent the most time in close proximity to the male their mother had spent the most time near when they were <1 year old. Observed discrepancies between female behavior in single and multi-male groups likely reflect different levels of postpartum intersexual conflict; in groups where paternity certainty and infanticide risk are both high, male-female interests align and females behave accordingly. This highlights the importance of considering individual and group-level variation when evaluating intersexual conflict across the reproductive cycle.